Diversity of Dictyostelid Cellular Slime Molds, Including Two Species New to Science, in Forest Soils of Changbai Mountain, China - Yue Zou; Jiangan Hou; Songning Guo; Changtian Li; Zhuang Li; Steven L. Stephenson; Igor N. Pavlov; Pu Liu; Yu Li (Microbiology Spectrum, 2022)
ABSTRACT Dictyostelid cellular slime molds (dictyostelids) are protists that are common inhabitants of most soils, where they feed upon bacteria. Changbai Mountain is the highest mountain in northeast China. Soil samples collected on Changbai Mountain yielded 11 isolates representing six species of dictyostelid samples. Two of these species (Dictyostelium robusticaule and Heterostelium recretum) were found to be new to science, based on morphology, SSU rDNA sequences, and an ATPase subunit 1 gene (atp1) phylogeny. The present study also demonstrated that the increased accuracy and lower costs associated with the use of atp1 sequences make them a complement of SSU rDNA sequences for identifying dictyostelids. Changbai Mountain is characterized by a higher diversity of dictyostelids than indicated by the few previous reports. Moreover, the data for Changbai Mountain, compared with comparable data for Taiwan, suggest that differences in diversity at the family level are possibly related to latitude. Mixed broadleaf-conifer forests produced more isolates and species than broadleaf forests at the same elevation and also had the highest species richness, which indicates an effect of vegetation on dictyostelids. However, the pattern of slightly decreasing diversity with increasing elevation in dictyostelids was also apparent. IMPORTANCE Dictyostelium robusticaule and Heterostelium recretum are two new species of dictyostelids reported in this study. The potential use of atp1 sequences is a complement of SSU rDNA sequences for the identifying dictyostelids. A pattern of slightly decreasing diversity with increasing elevation in dictyostelids was observed, with the conditions that exist at lower elevations apparently more suitable for dictyostelids, whereas differences of diversity observed at the family level are possibly related to latitude.